A Handbook for Scholars - Leunen, Mary-Claire van (Alfred A. Knopf, 1978)
A Handbook for Scholars also provides lively direction on a variety of usage and style questions, covering such topics as word choice, writing introductions and abstracts, capitalization, paragraphing, and the scholar's old nemesis, pedantry. It also offers advice on dealing with typists, editors, and printers, a handy "how to" section on creating academic CVs, and new chapters on computerized manuscript preparation.